Molecular dynamics investigations of mechanical behaviours in monocrystalline silicon due to nanoindentation at cryogenic temperatures and room temperature - Du, Xiancheng (Sci Rep, 2015)
Molecular dynamics simulations of nanoindentation tests on monocrystalline silicon (010) surface were conducted to investigate the mechanical properties and deformation mechanism from cryogenic temperature being 10 K to room temperature being 300 K. Furthermore, the load-displacement curves were obtained and the phase transformation was investigated at different temperatures. The results show that the phase transformation occurs both at cryogenic temperatures and at room temperature. By searching for the presence of the unique non-bonded fifth neighbour atom, the metastable phases (Si-III and Si-XII) with fourfold coordination could be distinguished from Si-I phase during the loading stage of nanoindentation process. The Si-II, Si-XIII, and amorphous phase were also found in the region beneath the indenter. Moreover, through the degree of alignment of the metastable phases along specific crystal orientation at different temperatures, it was found that the temperature had effect on the anisotropy of the monocrystalline silicon, and the simulation results indicate that the anisotropy of monocrystalline silicon is strengthened at low temperatures.